1982
DOI: 10.1007/bf01456410
|View full text |Cite
|
Sign up to set email alerts
|

Indefinite K�hler manifolds

Abstract: IntroductionLet M be a complex-n-dimensional indefinite Kfihler manifold, that means M is endowed with an almost complex structure J and with an indefinite Riemannian metric g, which is J-Hermitian, i.e., for all mEM g (Ju, Jv)=g(u,v) for all u,v~T"M, and VJ=O,where 17 denotes the Levi-Civita connection of g. It follows then, that J is integrable and the index of g is an even number 2s with 0 < s-< n. (The manifolds, maps .... will be understood to be of class CO~ Given these data, we shall use all the well-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
144
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 13 publications
(11 reference statements)
0
144
0
Order By: Relevance
“…Consider the semi-Euclidean space R("+x) with the indefinite Kahlerian structure (cf. Barros-Romero [1] PROOF. By direct calculations taking account of (1.5), (2.13), (2.14) and (4. [7].…”
Section: (33)mentioning
confidence: 97%
“…Consider the semi-Euclidean space R("+x) with the indefinite Kahlerian structure (cf. Barros-Romero [1] PROOF. By direct calculations taking account of (1.5), (2.13), (2.14) and (4. [7].…”
Section: (33)mentioning
confidence: 97%
“…Barros and Romero [2] showed that locally any complex space formM n s (4ǫ) is isometric holomorphically to C n s , CP n s (4ǫ) CH n s (4ǫ) according to ǫ = 0, ǫ > 0 or ǫ < 0.…”
Section: Lagrangian Submanifolds In Complex Space Formsmentioning
confidence: 99%
“…For more details, we refer the reader to [2]. LetM n s (4c) be an indefinite complex space form of complex dimension n and complex index s. The complex index is defined as the (complex) dimension of the largest complex negative definite vector subspace of the tangent space.…”
Section: Indefinite Complex Space Forms and Their Lagrangian Submanifmentioning
confidence: 99%
“…We refer to [2] for the construction of the standard models of indefinite complex space forms CP n s (4c), whenc > 0, CH n s (4c), whenc < 0 and C n s . For our purposes it is sufficient to know that there exist pseudo-Riemannian submersions, called Hopf fibrations,…”
Section: Indefinite Complex Space Forms and Their Lagrangian Submanifmentioning
confidence: 99%
See 1 more Smart Citation